Pengembangan Basis Data Untuk Mengelola Komponen Perkakas Bantu Perakitan - S Suwarsono (Jurnal Teknik Industri, 2002)
Welding assembly jig company's activities are classified as job-order. Their products (jigs & fixtures) were depending on type of product, which was assembled. There are loot-of variations of product designs, process planning, tools, shop-floor control etc. to handling all customer order. One of the solutions is standardization product, to reduce product variation and the control problems.